2015
DOI: 10.1177/1741143214549975
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and organizational citizenship behavior in the Arab educational system in Israel: The impact of trust and job satisfaction

Abstract: The present study aims to extend and integrate previous research on the mediating effects of trust in supervisor and job satisfaction on the relationship between transformational leadership style and organizational citizenship behavior (OCB). Drawing on previous research, we argue that transformational leadership impacts OCB directly and indirectly via employees' trust in supervisor and job satisfaction. Our sample comprised of 211 Arab male and female teachers in the Arab education system in Israel. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 47 publications
(63 reference statements)
4
64
1
3
Order By: Relevance
“…These research results which show that transformational leadership style significantly influences OCB of employees in mother and children hospitals in East Java, empirically support by Malik et al (2016) research results which conclude that there is a strong and positive relationship between leadership style and OCB, leadership style significantly contributes to the OCB enhancement, the democratic leadership style stimulates more OCB for employees. Another research by Jiang et al (2017), Nasra and Heilbrunn (2016) also have the same result. The study from Nasra and Heilbrun (2016) indicated a direct effect between transformational leadership and OCB.…”
Section: Influence Of Transformational Leadership Style To Ocbsupporting
confidence: 68%
“…These research results which show that transformational leadership style significantly influences OCB of employees in mother and children hospitals in East Java, empirically support by Malik et al (2016) research results which conclude that there is a strong and positive relationship between leadership style and OCB, leadership style significantly contributes to the OCB enhancement, the democratic leadership style stimulates more OCB for employees. Another research by Jiang et al (2017), Nasra and Heilbrunn (2016) also have the same result. The study from Nasra and Heilbrun (2016) indicated a direct effect between transformational leadership and OCB.…”
Section: Influence Of Transformational Leadership Style To Ocbsupporting
confidence: 68%
“…Besides, conjecturing about the proposal of this study, it is highlighted that few researches focused on OCB in educational institutions, even though there are some indicators that suggest there might be an impact on efficiency improvement and management in such originations (Bogler & Somech, 2004;Nasra & Heilbrunn, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…There is a large body of literature in relation to OCB that involves industries such as general services, banking and financial services, and manufacturing [28], the state electrical grid industry [29], the technology industry [30], and the education industry [31]. The antecedent variables of OCB have been explored from four aspects: individual characteristic variables, task characteristic variables, organizational characteristic variables, and leadership variables.…”
Section: Introductionmentioning
confidence: 99%